Molasses as fermentation substrate for levan production by Halomonas sp. - TOKSOY ÖNER, EBRU (SPRINGER, 2011)
Levan is a homopolymer of fructose with many outstanding properties like high solubility in oil and water, strong adhesiveness, good biocompatibility, and film-forming ability. However, its industrial use has long been hampered by costly production processes which rely on mesophilic bacteria and plants. Recently, Halomonas sp. AAD6 halophilic bacteria were found to be the only extremophilic species producing levan at high titers in semi-chemical medium containing sucrose, and in this study, pretreated sugar beet molasses and starch molasses were both found to be feasible substitutes for sucrose. Five different pretreatment methods and their combinations were applied to both molasses types. Biomass and levan concentrations reached by the Halomonas sp. AAD6 cells cultivated on 30 g/L of pretreated beet molasses were 6.09 g dry cells/L and 12.4 g/L, respectively. When compared with literature, Halomonas sp. was found to stand out with its exceptionally high levan production yields on available fructose. Molecular characterization and monosaccharide composition studies confirmed levan-type fructan structure of the biopolymers. Rheological properties under different conditions pointed to the typical characteristics of low viscosity and pseudoplastic behaviors of the levan polymers. Moreover, levan polymer produced from molasses showed high biocompatibility and affinity with both cancerous and non-cancerous cell lines.
Keywords: Levan; Fructan; Halomonas; Molasses; Sugar beet; Exopolysaccharide; STRUCTURAL-CHARACTERIZATION; ACID PRODUCTION; GUM PRODUCTION; CANE MOLASSES; TRACE-METALS; EXOPOLYSACCHARIDES; OPTIMIZATION; POLYSACCHARIDES; PRETREATMENT; NUTRIENTS